A Study Of Saudi Arabia’S Social Commentary Based On Photography Artworks - Abdullah, Alromih Roba (2022)
Photographers have their artistic creativity to express relevant social comments about the global social trend. In this respect, the current Saudi photographers have no exception. Compared to other developed countries, photography in Saudi Arabia has attracted little scientific and international attention. Therefore, this study seeks to unify communication by exploring the depiction of social commentary by Saudi photographers as they move to change the society. This study would determine the general perception of photographs produced by Saudi photographers. The artworks of Saudi artists from various art galleries in Saudi Arabia would be collected and analyzed by interviewing and distributing questionnaires to the public. This study utilized qualitative and quantitive methods to explore, interpret and analyze images. Feedback from the audience would be analyzed by NVivo and SPSS in order to identify recurring and emerging topics that the audience understands through social commentary images. Furthermore, this study would provide the communicative context for portraying social comments by Saudi photographers as an insight into the ideas, practices and attitudes of Saudi artists.